Constraint-induced movement therapy in stroke patients - Joanna Iłżecka (Kazimierz Wielki University, 2020)
Stroke is an important cause of disability and death of patients. The consequence of a stroke may be weakness of limbs or hemiplegia. Constraint-induced movement therapy (CIMT) is a technique of rehabilitation, whose mission is to provoke the patient to use the paretic upper limb. In the literature is presented many clinical studies on the effectiveness of CIMT therapy in patients after stroke. The aim of the work was a review of the literature on CIMT in stroke patients.